A116 EFFECTIVENESS OF A REMOTE PATIENT MONITORING PROTOCOL AIMING TO IMPROVE CARE FOR ULCERATIVE COLITIS PATIENTS. (15th March 2019) - Beilman, C L; Lytvyak, E; Garolera Molas, M; Peerani, F; Dieleman, L A; Kroeker, K; Wong, K; Fedorak, R; Halloran, B
Abstract: Background: Ulcerative colitis (UC) is a chronic, relapsing and remitting condition, characterized by inflammation and ulceration limited to the colon. Treatment of UC involves long-term maintenance therapy in an attempt to maintain remission and prevent disease flares. However, when patients are not experiencing symptoms, they can be lost to follow-up, decrease medication compliance, and delay or avoid regular visits with their gastroenterologist. This can be problematic because symptoms can have a poor correlation with disease activity. To ensure regular follow-up, our center has initiated a clinical outreach protocol in order to remotely monitor the disease activity of UC patients to potentially improve long-term patient care. Aims: The aim of our study is to assess the effectiveness of this protocol aiming to improve care for UC patients not on biologic therapy. Methods: UC outpatients at the University of Alberta IBD Clinic who had not been seen by their gastroenterologist in over six months were asked to participate in the protocol. Patients were excluded if they were taking biologic therapies or had a previous colectomy. As part of the protocol, patients completed a fecal calprotectin (FCP) stool test and routine blood work. Patients also completed a partial Mayo and a MARS-5 questionnaire to assess disease activity and medication adherence, respectively. Upon protocol completion, a summary of results was reviewed by their gastroenterologist, who was then asked to complete a survey regarding the utility of the protocol, as well as if the protocol led to a change in disease management. Results: Eighty-two patients (60% female) completed the protocol, with an average age of 52 years. Partial Mayo scores indicated clinical remission in 82% of patients. Decreased age was correlated with poor medication adherence (p=0.003), however FCP was not correlated with age (p=0.48). Sixteen (20%) patients in clinical remission according to Partial Mayo score had a FCL greater than 250 µg/g. Mean FCP of these patients was 798 µg/g. Based on results from the protocol, disease management was altered in 56% of patients. Of these patients, 25% had a clinic appointment booked, 31% had an endoscopy appointment booked, 9% had further investigative tests completed, and 9% had a delayed follow-up requested by their gastroenterologist due to quiescent disease activity. Conclusions: The remote patient monitoring protocol resulted in a change in disease management for the majority of UC patients. Furthermore, approximately 20% of patients who completed the protocol had elevated inflammatory markers despite none or few symptoms. Funding Agencies: Abbvie